Weak M-H center dot center dot center dot H-C and M-Cl center dot center dot center dot H-C interactions in orthometalated iridium and rhodium complexes - Huang, L. Y.; Aulwurm, Uwe; Heinemann, Frank Wilhelm; Knock, F.; Kisch, Horst (Chemistry - A European Journal, 1998)
Four different types of intramolecular MX ... C interactions have been observed in a series of five, structurally very similar, orthometalated iridium(III) and rhodium(III) complexes. For X=H and M=Ir or Rh, two-center or three-center interactions with MH ... HC distances of 1.80 - 1.83 (M = Ir) or 2.00 -2.20 Angstrom (M = Rh) were observed. For X=Cl the MCl ... HC distances of the three-center arrangement (M = Ir) were in the range of 2.38-2.60 Angstrom, while values of 2.41-2.89 Angstrom were found for the four-center geometry (M = Rh), These weak interactions open new perspectives for the mechanism of cyclometalations.
Keywords: azo compounds; hydrogen bonds; iridium; metalations; rhodium